FORMULA DAN IDEOLOGI PATRIARKI DALAM NOVEL ROMAN “SUNNY CHANDLER’S RETURN DAN DEMON RUMM” KARYA SANDRA BROWN SEBAGAI KAJIAN SASTRA POPULER - Yulistiyanti Yulistiyanti (Dinamika Bahasa dan Budaya, 2011)
Romance, one of popular fiction genres tells about love story which forms formula as plot and cultural convention. In Sandra Brown’s two romance novels plot is explored from exposition to resolution which conflicts develop the story. Characterization and setting help the writer find the cultural convention especially in American culture. It is not enough to discuss popular fiction without discussing the ideology. Here, patriarchy dominates romance novels. According to Dorothy Dinnerstein, there are six sexual arrangement which embody patriarchy domination as found in the two romance novels, Sunny Chandler’s Return and Demon Rumm. Key words: popular fiction, romance, formula, patriarchy, six sexual arrangements, Dorothy Dinnerstein